An Investigation of Digestion Methods for Trace Elements in Bauxite and Their Determination in Ten Bauxite Reference Materials Using Inductively Coupled Plasma‐Mass Spectrometry. Issue 2 (27th July 2015) - Zhang, Wen; Qi, Liang; Hu, Zhaochu; Zheng, Cunjiang; Liu, Yongsheng; Chen, Haihong; Gao, Shan; Hu, Shenghong
Abstract : Trace elements from samples of bauxite deposits can provide useful information relevant to the exploration of the ore‐forming process. Sample digestion is a fundamental and critical stage in the process of geochemical analysis, which enables the acquisition of accurate trace element data by ICP‐MS. However, the conventional bomb digestion method with HF/HNO3 results in a significant loss of rare earth elements (REEs) due to the formation of insoluble AlF3 precipitates during the digestion of bauxite samples. In this study, the digestion capability of the following methods was investigated: (a) 'Mg‐addition' bomb digestion, (b) NH4 HF2 open vessel digestion and (c) NH4 F open vessel digestion. 'Mg‐addition' bomb digestion can effectively suppress the formation of AlF3 and simultaneously ensure the complete decomposition of resistant minerals in bauxite samples. The addition of MgO to the bauxite samples resulted in (Mg + Ca)/Al ratios ≥ 1. However, adding a large amount of MgO leads to significant blank contamination for some transition elements (V, Cr, Ni and Zn). The NH4 HF2 or NH4 F open vessel digestion methods can also completely digest resistant minerals in bauxite samples in a short period of time (5 hr). Unlike conventional bomb digestion with HF/HNO3, the white precipitates and the semi‐transparent gels present in the NH4 HF2 and NH4 F digestion methods could be efficiently dissolved by evaporation with HClO4 . Based on these three optimised digestion methods, thirty‐seven trace elements including REEs in ten bauxite reference materials (RMs) were determined by ICP‐MS. The data obtained showed excellent inter‐method reproducibility (agreement within 5% for REEs). The relative standard deviation (% RSD) for most elements was < 6%. The concentrations of trace elements in the ten bauxite RMs showed agreement with the limited certified (Li, V, Cr, Cu, Zn, Ga, Sr, Zr and Pb) and information values (Co, Ba, Ce and Hf) available. New trace element data for the ten RMs are provided, some of which for the first time.